The expression `(3*c^-4*d^5)^2*12*c*d^-4` has to be simplified.

`(3*c^-4*d^5)^2*12*c*d^-4`

Use the following formulas `(x^b)^c = x^(b*c)` , `x^a*x^b = x^(a+b)`

= `3^2*c^(-2*4)*d^(2*5)*12*c*d^-4`

= `9*12*c^(-8 + 1)*d^(2*5 - 4)`

= `108*c^-7*d^6`

**The simplified form of the expression `(3*c^-4*d^5)^2*12*c*d^-4` = `108*c^-7*d^6` **

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now